Black Carbon Aerosol over a High Altitude (~ 4.52 km) Station in Western Indian Himalayas - Chaubey, Jai Prakash; Babu, S Suresh; Gogoi, Mukunda M; Kompalli, Sobhan Kumar; Sreekanth, V; Moorthy, K Krishna; Prabhu, Tushar P (Journal of the Institute of Engineering, 2012)
Continuous measurements of mass concentration of Black Carbon (BC) aerosols, measured from a high altitude (~ 4.5 km above msl) location, Hanle (32.78°N, 78.95°E) in the western Himalayas, during August 2009 to July 2010 have been examined. The day-to-day variations in BC mass concentration (MB) were rather subdued in winter months while quite conspicuous during the spring months. It showed a well defined annual cycle with a maximum (109 ± 78 ng m-3) during spring and minimum during the winter (66 ± 62 ng m-3) season with an annual average MB of 78 ± 64 ng m-3. Examining the frequency distribution, it was found that 64 % of the values were below annual mean MB showing a rather pristine nature for this near free tropospheric region. Trajectory clustering and concentration weighted trajectory (CWT) analysis indicated that, most of the year, the site is influenced from the advection from west and south west Asian locations and only for a small period from the Indo-Gangetic Plains (IGP). The observations are compared with other high altitude measurements, over the globe in general and around the Himalayan region. DOI: http://dx.doi.org/10.3126/jie.v8i3.5930 JIE 2011; 8(3): 42-51